Economic policies and unemployment dynamics in Europe - Henry, S. G. B.; Snower, Dennis J. (Washington, D.C., U.S.A. : International Monetary Fund, 1996)
This book, edited by S.G.B. Henry and Dennis J. Snower, examines the high unemployment that has plagued five European countries- France, Germany, Italy, Spain, and the United Kingdom- for more than a decade. Its methodology focuses on the mechanisms that prevent employers and employees from adjusting promptly to changing market opportunities. Chief among these mechanisms are outdated economic structures, the power of labor unions, rising nonwage labor costs, and the disparity between unemployed workers and available jobs. Although cross-country differences indicate that there is no common cause for joblessness in Europe, the book discusses a unique characteristic of the European labor market- that unemployment not only rises during recessions, but does not fall when economic weaknesses are overcome.
Includes bibliographical references.
rpm 31/08/16
Loans
Keywords: Unemployment; Labor policy; Labor market; Europe